Roadmap for the Ukrainian hydrogen strategy, the course for implementation in Europe - I. D. Bahrii; O. O. Popov; Ia. M. Kryl; Yu. F. Rudenko; I. L. Koliabina; I. Ye. Mamyshev (Мінеральні ресурси України)
To date, in support of the European Green Deal’s ambition to achieve carbon neutrality by 2050, the European Commission presented the EU Hydrogen Strategy in July 2020, looking at how hydrogen can support the decarbonisation of the economy and promote EU industrial leadership in this sector. Hydrogen as a clean energy fuel prioritises the deployment of renewable energy components needed for sectors such as transport and industry, and sets clear targets for the EU for the installation of electrolysers or pure hydrogen production. Moreover, this policy aims to rapidly reduce dependence on Russian fossil fuels. The authors propose to implement a pre-delta strategy for the safe use of water resources to produce process water for green hydrogen production and to safely discharge retentate into marine aquatic areas. This will provide a good basis for the sustainable use of water resources without impacting on climate change. The integrity of Europe’s river basins and ecosystems, including water balance and water chemistry, will be fully ensured. Using the example of safe use of water resources in the deltas of European river systems, we can obtain a significant amount of green hydrogen, as demonstrated by the calculations presented in the article.